Acoustics in South African classrooms: Regulations versus reality. Issue 1 (March 2022) - van Reenen, Coralie; Plessis, Chrisna du
This research set out to broaden the pool of evidence regarding the acoustic conditions at schools in South Africa. A review of local and international literature, standards and design guidelines shows that the ideal classroom acoustic conditions of 35 dBA ambient and 0.7 s reverberation time are required to enable a suitable environment for teaching and learning. A review of local literature revealed a very small body of knowledge regarding actual acoustic conditions and monitoring of classroom acoustics and that these cases demonstrated ambient noise levels in classrooms (whether occupied or unoccupied) to be above the recommendations of the relevant South African National Standard (SANS 10103). The limited local research promted the need for this case study. The findings of a province-wide survey of urban schools showed that traffic noise is the main source of noise disturbance in schools. A case study of five schools showed that the average outdoor noise level at schools exposed to traffic throughout the day is 63.3 dBA and the average indoor noise level at these schools when classrooms are unoccupied is approximately 58 dBA, which is significantly higher than the requirement. The reverberation time in classrooms was between 0.6 and 1.75 s. It is concluded that the current acoustic conditions in South African urban schools is poor when evaluated against the South African National Standards. However, since this is based on only five case studies, a broader study is required to understand the general conditions and establish suitable mitigation measures.